Analysis of the Daily Behavior of Javan Gibbons (Hylobates moloch) at the Lombok Wildlife Park Ex-Situ Conservation Institute - Rahayu, Widya; Ichsan, Andi Chairil; Syaputra, Maiser (Jurnal Biologi Tropis, 2025)
The Javan gibbon (Hylobates moloch) is a primate endemic to Java Island that plays a crucial ecological role as a seed disperser and indicator of rainforest health. This study aims to analyze the daily behavioral patterns of the Javan gibbon (Hylobates moloch) at the ex-situ conservation site Lombok Wildlife Park to assess its expression of natural behaviors and welfare conditions. The research was conducted from September 2024 to January 2025 using the ad libitum observation method on a single male individual. Observations were carried out once daily from 09:00 to 17:00 for seven consecutive days each week. Data were analyzed descriptively and quantitatively through ethogram presentation and frequency percentage calculations of behavioral occurrences. The results showed a dominance of arboreal locomotion behaviors: brachiation occurred 126 times (38.77%), climbing 47 times (14.46%), and descending 43 times (13.23%). Foraging and social behaviors were moderately observed feeding 27 times (8.31%) and playing 26 times (8.00%) while self-maintenance (grooming) occurred 13 times (4.00%) and resting 15 times (4.62%). Excretion frequency was low: urination 6 times (1.85%) and defecation 2 times (0.62%). These findings indicate that the enclosure structure supports natural arboreal behavior, but additional foraging stimulation and enrichment are needed to prevent boredom and enhance long-term welfare. Recommendations include improving environmental enrichment complexity, regular evaluation of vertical structures, and further research on Javan gibbon welfare standards in ex-situ conservation facilities.